МЕТОДИКА ВИЗНАЧЕННЯ МІЖПОВІРОЧНОГО ІНТЕРВАЛУ ЗАСОБІВ ВИМІРЮВАННЯ НА ОСНОВІ КОНЦЕПЦІЇ НЕВИЗНАЧЕНОСТІ - Васілевський, О.М. (Інститут електродинаміки НАН України, Київ, 2014)
A method for determining the recalibration interval measurement tools, which is based on the use of the concept of measurement uncertainty analysis of experimental data with the metrological certification. Results of testing procedures to determine the recalibration interval measuring torque motors. References 15, tables 3.